The impact of the online knowledge library: Its use and impact on the production of the portuguese academic and scientific community (2000-2010) - Costa, Teresa (2014)
In recent years several initiatives have taken place to promote universal access to the Information and Knowledge Society. It was in this context that in 2004 the Online Knowledge Library (b-on) was launched in Portugal. With it, it became easier to get access to full text international scientific publications. This study aims to present and analyse some of the statistical and bibliometric indicators of the Portuguese scientific output seeking to evaluate its link it with b-on. It was analysed the usage of b-on resources by the public universities members of the consortium from 2004 to 2010, and we chose as sample the five universities with more downloads per FTE (full time equivalent).In addition to the usage data of the consortium, we used the Web of Science (WoS) from which we identified the articles indexed by the five Portuguese universities affiliated between 2000-2010.Thus, and through a quantitative methodology, we identified the scientific production per subject area, international cooperation and scientific journals with the highest number of published articles, among others. We conclude that the availability and access to electronic resources contributes to the increased of the scientific productivity of the universities and that the study and analysis of its use and output are essential.